Bioethical considerations for algal biotechnology - Vasileva, Ivanina; Ivanova, Juliana; Alexandrov, Svetoslav (Bangladesh Journal of Bioethics, 2018)
In this manuscript we discuss different aspects and applications of algal biotechnology and how they are seen through the prism of bioethics. We review how algae have been considered to solve problems on Earth and to ease human suffering. We also take a look at the current state of the production of algal biomass and we offer our suggestions and considerations based on the fact that the biomass is an expensive product and yet its quality is very good.